The Practice and Willingness of Women Towards Opportunistic Screening for Breast and Cervical Cancers in Sichuan Province, China: A Cross-Sectional Study - Li H; Huang M; Yang Y; Tang J; Ye Y (Dove Medical Press, 2023)
Hui Li,1 Mingquan Huang,2 Yonglian Yang,3 Jun Tang,3 Yunli Ye1 1School of Public Health, Southwest Medical University, Luzhou, Sichuan, People's Republic of China; 2Department of Breast Surgery, Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of China; 3School of Basic Medical Science, Southwest Medical University, Luzhou, Sichuan, People's Republic of ChinaCorrespondence: Yunli Ye, Southwest Medical University, No. 1 Section 1, Xianglin Road, Longmatan District, Luzhou, Sichuan, People's Republic of China, Tel/Fax +86 0813 3161797, Email yunliye072@swmu.edu.cnPurpose: To understand the practices and willingness of Chinese women to undergo opportunistic screening for breast cancer (BC) and cervical cancer (CC).Patients and Methods: From July to August 2021, a cross-sectional study of 1446 women from six cities in Sichuan Province, China, was conducted. A questionnaire was used to investigate practices, willingness, and barriers to opportunistic screening for BC and CC. Furthermore, potential factors for opportunistic screening willingness were analyzed using the chi-squared test and logistic regression.Results: During their lifetime, 312 (21.6%) and 388 (26.8%) women had undergone opportunistic screening for BC and CC, respectively. There were 1069 (73.9%) women willing to accept physician-recommended screening during a medical visit, while 835 (57.7%) were willing to have a voluntary screening at a healthcare institution. The main barriers to reluctance to participate in physician-recommended and voluntary screenings were "no symptoms; hence, no need for screening" and "unwillingness or difficulty in paying screening cost". Ethnic minorities, lower education levels, and menopause were inversely associated, whereas awareness of the screening methods and eligibility for screening were positively associated with physician-recommended and voluntary screenings (P < 0.05). Furthermore, awareness of "two-cancers" screening was positively associated with physician-recommended screening (P < 0.05).Conclusion: BC and CC opportunistic screening rates in Sichuan Province were low. The willingness to undergo physician-recommended screening was high, while that towards individual initiative screening was low. Public health education should be strengthened to increase cancer prevention awareness and knowledge of cancer screening, especially for women with low education, ethnic minorities, and post-menopause, for whom tailored interventions are suggested. In addition, novel ways of sharing screening costs need to be explored.Keywords: physician-recommended screening, voluntary screening, "two-cancers" screening, behavior, willingness